Does early intervention reduce the number of elderly people with dementia admitted to institutions for long term care?. Issue 6781 (13th April 1991) - O'Connor, D W; Pollitt, P A; Brook, C P; Reiss, B B; Roth, M
Abstract : OBJECTIVE–To test whether early diagnosis and practical help reduce the number of elderly people with dementia admitted to institutions. DESIGN–Controlled trial of effect of help from a multidisciplinary team on admission rates of people with dementia. SETTING–Seven general practices in Cambridge. SUBJECTS–2889 subjects aged 75 and over, of whom 159 were identified as having dementia with a two stage community survey. Eighty six subjects were referred for extra help if they or their supporters wished. The other 73 subjects had access to the usual services and served as controls. INTERVENTION–Subjects and families in the action group were offered a wide range of help, including financial benefits, physical aids, home helps, respite admissions, practical advice, and psychiatric assessments. MAIN OUTCOME MEASURE–Permanent admission to long term care within two years after diagnosis. RESULTS–Early intervention did not affect admission rates in subjects who lived with supporters. By contrast, nine of the 14 (64%) subjects with moderate or severe dementia living alone were admitted in the action group in the study's second year compared with only one of 13 (8%) controls (p = 0.004). CONCLUSIONS–Some people with moderate or severe dementia who lived alone and were at serious risk may have been identified earlier by the resource team. Without the team these people would not have become known to the responsible authorities until families, neighbours, and wardens became unable to cope. The study was conducted during the team's formative period, however, and greater experience might have allowed some subjects to remain at home for longer.